Effective Strategies for Teaching English to Elementary School Students at SDN 02 Sukamulya Cikarang Utara: Penelitian - Edri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify effective strategies for teaching English to young learners at SDN 02 Sukamulya Cikarang Utara. Focusing on student engagement and language acquisition, it explores interactive and multimodal methods suited to primary school settings in Indonesia. Using qualitative methods—document analysis, interviews with English teachers, and classroom observations—the study highlights key strategies that enhance learning. These include the use of visual aids (e.g., flashcards, posters), game-based activities (e.g., “Simon Says”), and song-based exercises (e.g., “Head, Shoulders, Knees and Toes”). Storytelling with repetitive sentence structures helps reinforce vocabulary and grammar, while code-switching between English and Bahasa Indonesia improves comprehension and reduces anxiety. The findings emphasize the importance of teacher creativity, adaptability, and varied materials in building a fun and effective learning environment. These insights offer valuable guidance for educators aiming to improve English instruction in similar primary education contexts